AutoDock-IPS: An Automated Docking for Mobile Robot Based on Indoor Positioning System - Wardhana, Dimas Aditya Putra; Happyanto, Dedid Cahya; Purwanto, Era; Akbar, Gilang Ekavigo Astafil; Putra, Karisma Trinanda (Universitas Muhammadiyah Yogyakarta, 2021)
Mobile robots are proven to be reliable in supporting the human tasks by using a computerized system that minimizes human errors. However, recharging the battery in these robots is still performed manually by the user. Therefore, to extend their lifetime, an indoor automatic docking system ‘AutoDock-IPS’ is created for mobile robot to charge its battery automatically. The automatic docking system determines the location of the docks (i.e., charging stations) so that, prototype can immediately navigate to them. Experiments were carried out to validate the docking method by utilizing a compass module as a direction sensor and a rotary encoder as a displacement indicator. These sensors are combined into a robust indoor positioning system. The results show that the prototype can find the fastest route to the docking station to perform battery charging procedure.